The Description Of Risk Level Disability Due To Lower Back Pain Employees At Logistics Company Site J Surabaya 2023 - Auliya, Nurul; Dwi Rahma Rusdy, Mirta; Handayani, Putri; Situngkir, Decy (Sean Institute, 2024)
Musculoskeletal disorders (MSD) are diseases that are identically caused by work. One of the musculoskeletal disorders is low back pain (LBP). Factors causing LBP are unergonomic positions when working, worker's age, gender, and education. Site logistics company J Surabaya is a company that operates in the field of product storage services and distribution of goods from J customers to several distributors. In its operational processes, several employees were found to be carrying out unergonomic actions, apart from that, many employees were experiencing lower back pain. As a result of this condition, the company suffered losses. This research was conducted to know the risk of disability due to lower back pain in employees at the logistics company site J Surabaya. The research method used was univariate descriptive research by taking data on employees who complained of lower back pain using the ODI questionnaire. The data analysis used is cross-tab. The results of the questionnaire obtained data to describe the risk of disability due to lower back pain in employees at the logistics company site J Surabaya, the highest was in the male category aged > 30 years at 95.5% (21 employees), the lowest was female 2 employees 50% good at ages < 30 years and > 30 years. Based on age at >30 years old with a percentage of 95.5% (21 employees) and <30 years old with (4.5%) 1 employee. Based on employee gender, 90.9% are male (20 employees) and 9.1% female (2 employees).